Rute Distribusi Limbah Medis Covid-19 dengan Metode VRPTW dan Nearest Neighbor - Siska Amonalisa Silalahi (Institut Transportasi dan Logistik Trisakti, 2021)
Medical waste classified as hazardous and toxic (B3). Medical waste cannot be compared to household waste, its needs specific treatment. According to several newspapers, there is a lot of medical waste which handling mixed with household waste. In Surabaya, the number of medical wastes in 2019 reached 8 tons per day, this number certain to increase exponentially in the current Covid19 pandemic. It is important to manage well the medical waste of Covid19. To support the medical waste management of Covid19, it is necessary to design distribution route for Covid19 medical waste. The design of distribution route for Covid19 medical waste will use the Vehicle Routing Problem with Time Window (VRPTW) method and the Nearest Neighbor (NN) algorithm. The design of distribution route aims to obtain an optimal route that can minimize the distribution cost of Covid19 medical waste.